The Utility of a Three-Dimensional Approach with T-Shaped Osteotomy in Osseous Genioplasty - Jung Jae Jegal; Seok Joo Kang; Jin Woo Kim; Hook Sun (Archives of Plastic Surgery, 2013)
Background  Facial beauty depends on the form, proportion, and position of various unitsof the face. In terms of the frontal view and facial profile, the chin is the most prominentaesthetic element of the lower third of the face. Many methods have been implemented toobtain good proportions ofthe lowerface. In thisstudy,we applied the T-shaped genioplastymethod to correcting chin deformities.Methods  All of the procedures in 9 cases were performed under general anesthesia. Forgenioplasty, a horizontal cutting line and 1 or 2 vertical cutting lines were drawn 5 mmbelowthe mentalforamen. Osteotomed bone segments ofthe chinwere used for horizontalwidening using bone grafts or for horizontal shortening. Likewise, they were used as bonegraftsfor vertical lengthening or verticalshortening. The bone segments were approximatedin themidline and held in place usingminiplates.Results  The postoperative appearance of the 9 cases showed that the lower third of theface had been naturally changed. At the same time, vertical lengthening or shortening, andhorizontal widening or shortening could be implemented during the operation. Satisfactoryresults were obtained based on reviews of the patients’ preoperative and postoperativephotographs. The patientswere also satisfiedwith the outcomes.Conclusions  Using T-shaped genioplasty, we efficiently adjusted the shape and position ofthe chin to obtain good proportions of the lower face and change its contour to obtain anaesthetically appealing ovalface in accordancewith East Asians’ aesthetic preferences.